Online Learner Self-Regulation: Learning Presence Viewed through Quantitative Content- and Social Network Analysis - Shea, Peter; Hayes, Suzanne; Uzuner Smith, Sedef; Vickers, Jason; Bidjerano, Temi; Gozza-Cohen, Mary; Jian, Shou-Bang; Pickett, Alexandra M.; Wilde, Jane; Tseng, Chi-Hua (International Review of Research in Open and Distributed Learning, 2013)
This paper presents an extension of an ongoing study of online learning framed within the community of inquiry (CoI) model (Garrison, Anderson, & Archer, 2001) in which we further examine a new construct labeled as learning presence. We use learning presence to refer to the iterative processes of forethought and planning, monitoring and adapting strategies for learning, and reflecting on results that successful students use to regulate their learning in online, interactive environments. To gain insight into these processes, we present results of a study using quantitative content analysis (QCA) and social network analysis (SNA) in a complementary fashion. First, we used QCA to identify the forms of learning presence reflected in students’ public (class discussions) and more private (learning journals) products of knowledge construction in online, interactive components of a graduate-level blended course. Next, we used SNA to assess how the forms of learning presence we identified through QCA correlated with the network positions students held within those interactional spaces (i.e., discussions and journals). We found that the students who demonstrated better self- and co-regulation (i.e., learning presence) took up more advantageous positions in their knowledge-generating groups. Our results extend and confirm both the CoI framework and previous investigations of online learning using SNA.